Analysis of dynamics of scientometric indicators of journal “Morphologia” in Russian Index of Scientific Citation - Pototskaya O.Yu.; Tverdokhleb I.V. (Морфологія, 2014)
Background. Scientometric indicators are very useful for the comparative analysis of different scientists, organizations, journals, etc. Their calculation and dynamics are also very helpful for editorial office in improvement of the quality of scientific periodicals. Objective. To analyze the dynamic of scientometric indicators of journal “Morphologia” in Russian Index of Scientific Citation system. Methods. We have examined further indicators: biennial and five-year impact-factors with and without accounting of self-citations, biennial and five-year index of self-citation during the period 2008-2013 years. Results. Since the beginning of publication of the journal the lowest level of indicators was fixed in 2012 year – 0.065 and 0.049 for biennial and five-year impact-factors without accounting of self-citations, respectively. In turn, 2013 year was characterized by maximal value of these indices – 0.135 and 0.143, respectively. Biennial and five-year indices of self-citation showed the same dynamics with stable decrease to the level of 25% and 10.3%, respectively. Conclusion. Taken together scientometric indicators of journal “Morphologia” during investigated period reflects positive dynamics. Citation: Pototskaya OYu, Tverdokhleb IV. [Analysis of dynamics of scientometric indicators of journal “Morphologia” in Russian Index of Scientific Citation]. Morphologia. 2014;8(4):7-11. Russian.